Dampak Pandemi Covid-19 terhadap Pertumbuhan Ekonomi Indonesia Tahun 2020-2021 - Mashita, Juni (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The Covid-19 pandemic significantly impacted Indonesia’s economy during 2020-2021. With GDP contracting by -2.07% in 2020, the pandemic led to sharp declines in major sectors such as tourism, trade, and transportation. The unemployment rate rose to 7.07%, while poverty increased to 10.19%. The government launched the National Economic Recovery Program (PEN) to mitigate the pandemic's effects through social assistance, MSME incentives, and healthcare support. Although these policies drove economic recovery in 2021, achieving a GDP growth of 3.69%, challenges such as bureaucracy and unequal budget distribution persisted. Furthermore, the pandemic accelerated digital transformation, positioning the digital sector as a crucial pillar of economic recovery. This study concludes that the pandemic not only exposed structural weaknesses in Indonesia's economy but also unveiled opportunities to build a more resilient and sustainable economy.